Lysine 63-linked Ubiquitination Modulates Mixed Lineage Kinase-3 Interaction with JIP1 Scaffold Protein in Cytokine-induced Pancreatic β Cell Death - Humphrey, Rohan K. (American Society for Biochemistry and Molecular Biology, 2013)
The mixed lineage kinase MLK3 plays a crucial role in compromising mitochondrial integrity and functions as a proapoptotic competence factor in the early stages of cytokine-induced pancreatic β cell death. In an effort to identify mechanisms that regulate MLK3 activity in β cells, we discovered that IL-1β stimulates Lys-63-linked ubiquitination of MLK3 via a conserved, TRAF6-binding peptapeptide motif in the catalytic domain of the kinase. TRAF6-mediated ubiquitination was required for dissociation of inactive monomeric MLK3 from the scaffold protein IB1/JIP1, facilitating the subsequent dimerization, autophosphorylation, and catalytic activation of MLK3. Inability to ubiquitinate MLK3, or the presence of A20, an upstream Lys-63-linked deubiquitinase, strongly curtailed the ability of MLK3 to affect the proapoptotic translocation of BAX in cytokine-stimulated pancreatic β cells, an early step in the progression toward β cell death. These studies suggest a novel mechanism for MLK3 activation and provide new clues for therapeutic intervention in promoting β cell survival.